2004
DOI: 10.1161/01.hyp.0000117153.48029.d1
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Is an Independent Predictor for the Progression of Aortic Wall Calcification in Patients With Controlled Hyperlipidemia

Abstract: Abstract-Recent epidemiological studies suggested that calcifications of the aorta and the coronary arteries are important predictors for cardiovascular morbidity and mortality. However, the relation between blood pressure components and the progression of vascular wall calcification has remained unclear. We quantified calcium deposits in the abdominal aorta as the percentage of aortic calcification volume (%ACV) using computed tomography in patients with hyperlipidemia. Those who had aortic calcification were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 30 publications
1
56
1
1
Order By: Relevance
“…In addition, the relationship between lipids and aortic calcification is likely to remain controversial, because several studies have indicated that no correlation is present between abdominal aortic calcification and serum lipid components 34) . In this study, there was no association between AAC grade and the presence of dyslipidemia, although our cohort included 67.8% patients with dyslipidemia, including statin users (18%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relationship between lipids and aortic calcification is likely to remain controversial, because several studies have indicated that no correlation is present between abdominal aortic calcification and serum lipid components 34) . In this study, there was no association between AAC grade and the presence of dyslipidemia, although our cohort included 67.8% patients with dyslipidemia, including statin users (18%).…”
Section: Discussionmentioning
confidence: 99%
“…5. Second, an index of lower abdominal aortic calcification using a plain CT scan was also measured, as previously described 18) . Using the TES-100 image software program, the percentage of calcified area against the whole vascular area was calculated from images of four consecutive slices just above the bifurcation of the common iliac arteries.…”
Section: Quantitative Assessment Of Abdominal Aortic Calcificationmentioning
confidence: 99%
“…5 These studies have correlated the calcification with hemodynamic indices and have established the link between calcification and PP (β=0.4, P<0.01). 6 One study reported a greater number of calcified lesions in the descending thoracic aorta than its other segments, especially the ascending thoracic aorta. 7 Histopathological studies have demonstrated, albeit in a relatively young and healthy selected cohort, that elastic fiber concentration progressively decreases…”
Section: 3mentioning
confidence: 99%
“…In a separate study and compared with SBP, DBP, and MAP, PP was the strongest predictor of the progression of calcium attributable to atherosclerosis in the abdominal aorta. 27 Conversely, MAP has been found to be associated with incident CVD in younger but not older men. 28 These results, combined with previous reports on PP, 29 demonstrate increasing evidence that among individuals 50 years of age or older, PP is an independent predictor of atherosclerosis, coronary artery disease, and CHD.…”
Section: Discussionmentioning
confidence: 99%